Teaching and Learning during a Global Pandemic: Perspectives from Elementary School Teachers and Parents - Karrie E. Godwin; Freya Kaur; Susan Sonnenschein (MDPI AG, 2023)
COVID-19 has had a major impact on education, with many children attending school online for more than a year. To understand the implications of online learning for U.S. teachers (Study 1; N = 49) and families (Study 2; N = 189) of elementary school students, we administered a survey in spring 2021, about one year into the pandemic. Participants answered questions about the instructional modality and format, challenges managing instruction, and children's attention and learning. Comparing virtual to in-person instruction (pre-COVID-19) showed: (1) teachers reported the quantity of virtual instruction was less than in-person instruction and children were more off-task; (2) parents reported greater stress managing virtual instruction with fewer than half the children completing online lessons independently; and (3) parents reported that children exhibited mild-frustration during both virtual and in-person instruction, but children enjoyed learning in-person more. Understanding teachers' and families' experiences with virtual instruction will help elucidate potential factors contributing to pandemic-related learning losses, enabling more targeted support.